Dynamic, Helminth-Induced Immune Modulation Influences the Outcome of Acute and Chronic Hepatitis B Virus Infection. (25th December 2019) - Loffredo-Verde, Eva; Bhattacharjee, Sonakshi; Malo, Antje; Festag, Julia; Kosinska, Anna D; Ringelhan, Marc; Rim Sarkar, Sabrina; Steiger, Katja; Heikenwaelder, Mathias; Protzer, Ulrike; Prazeres da Costa, Clarissa U
Abstract: Background: Chronic hepatitis B develops more frequently in countries with high prevalence of helminth infections. The crosstalk between these 2 major liver-residing pathogens, Schistosoma mansoni and hepatitis B virus (HBV), is barely understood. Methods: We used state-of-the-art models for both acute and chronic HBV infection to study the pathogen-crosstalk during the different immune phases of schistosome infection. Results: Although liver pathology caused by schistosome infection was not affected by either acute or chronic HBV infection, S mansoni infection influenced HBV infection outcomes in a phase-dependent manner. Interferon (IFN)-γ secreting, HBV- and schistosome-specific CD8 T cells acted in synergy to reduce HBV-induced pathology during the TH 1 phase and chronic phase of schistosomiasis. Consequently, HBV was completely rescued in IFN-γ-deficient or in TH 2 phase coinfected mice demonstrating the key role of this cytokine. It is interesting to note that secondary helminth infection on the basis of persistent (chronic) HBV infection increased HBV-specific T-cell frequency and resulted in suppression of virus replication but failed to fully restore T-cell function and eliminate HBV. Conclusions: Thus, schistosome-induced IFN-γ had a prominent antiviral effect that outcompeted immunosuppressive effects of TH 2 cytokines, whereas HBV coinfection did not alter schistosome pathogenicity. Abstract : The significance of concomitant HBV and S mansoni infection is a controversial topic. The authors demonstrate that the immunological interaction of 2 prominent, liver-residing pathogens, HBV and S mansoni, results in reduced viral replication in a dynamic schistosome-phase dependent manner.